Exploring the effect of tea dust magnetic biochar on agricultural crops grown in polycyclic aromatic hydrocarbon contaminated soil - Sonowal Songita; Prasad Ram (Green Processing and Synthesis)
Magnetic biochar is a newly discovered novel material synthesized by adding an external magnetic field to conventional biochar. It exhibits dynamic properties like large surface area, porous cavities, ductility, and many functional groups on the surface. Due to the presence of these features, magnetic biochar has tremendous applications in various fields. The magnetic separation property is particularly beneficial for removing contaminants from soil. Much research has been done in this field, and positive results have been shown in the remediation of heavy metals, polycyclic aromatic hydrocarbons (PAHs), and organic contaminants from soil. Removal of these environmental contaminants is essential because they degrade the soil quality by alternating the physico-chemical activity and microbial diversity. Later, it makes the soil unfavorable for the growth of crops. Although much research has been done in this field and succeeded, little attention has been paid to the effect of magnetic biochar on plant growth. Therefore, in this research, we have synthesized the magnetic biochar from tea dust and applied it to the PAH-contaminated soil to explore the effect of tea dust magnetic biochar on the growth of barley plants.